Analisis Tolok Ukur Non Konstitusi dalam Pengujian Undang-Undang Terhadap Undang-Undang Dasar 1945 - . Baharudin (Universitas Bandar Lampung (UBL), 2012)
This research study about Analysis Measuring Rod of Non Constitution In Examination Of Code To Constitution 1945, problems focus cover: rule condition and reason of non constitution can be made measuring rod in examination of code to Constitution 1945 at Lawcourt Constitution. Result of research of menunjukan that there are basis for idea enabling of usage of[is non constitution in decision, that is is: First, Lawcourt Constitution in testing Code obliged to dig values punish and sense of justice which live in society pursuant to UUD 1945 as highest elementary law and also Code as formulation of UUD 1945. Both, Praktik Lawcourt Constitution in former decision No. 27/PUUVII/2009, 16 June 2010 for example expressing